The case for qualitative research - Fischer, Eileen; Guzel, Gulay Taltekin (Journal of Consumer Psychology, 2023)
Abstract This paper makes the case that there is considerable untapped potential for qualitative research to make theoretical contributions that will advance our collective insights on consumer psychology. The paper explains some features that distinguish qualitative research from other approaches and addresses some common misperceptions about it. It explains why qualitative research—which is geared toward theory development and refinement—can be such as useful took in the kit of researchers seeking insights on consumer psychology. It then outlines a qualitative research process suitable for crafting conceptual contributions to consumer psychology and offers a set of criteria that are appropriate and inappropriate for adjudicating qualitative research of this kind. In all, we make the case that the conditions are in place for JCP to be a vibrant platform for publishing research based on qualitative methods.